Genetically encoded RNA photoswitches as tools for the control of gene expression - Jäschke, Andres (FEBS letters, 2012)
An important goal in chemical and synthetic biology is controlling the expression of defined sets of genes by external stimuli, and one of the most attractive stimuli is light. Current approaches to the photocontrol of biological processes utilize photoresponsive proteins. In this article, I will illustrate the prospects of synthetic systems in which the receptor is a photoresponsive nucleic acid, and will review the different tools already in place to develop photoresponsive systems based on RNA. A particular focus is on genetically encoded photoswitches that can be expressed in prokaryotic or eukaryotic cells, and respond to photoisomerizable, cell-permeable small molecules.
Available online 31 May 2012
First published: 31 May 2012
Gesehen am 25.06.2018